Ecology and conservation of the maned wolf : multidisciplinary perspectives - Consorte-McCrea, Adriana G.; Santos, Eliana Ferraz (CRC Press, 2013)
Wolves are controversial figures worldwide and much effort has focused on how to conserve them while addressing public concerns. With its solitary habits and fruit-eating diet, the endangered maned wolf roams the South American grasslands and swamps, playing a vital part in maintaining biodiversity hotspots. Compared to the grey wolf, little is known about its relationship with local people and the environment and the reasons for its decline, making research about this unique species an urgent concern. Ecology and Conservation of the Maned Wolf: Multidisciplinary Perspectives gathers the work o.